2014
DOI: 10.1111/emr.12091
|View full text |Cite
|
Sign up to set email alerts
|

Flows for native fish in the Murray‐Darling Basin: lessons and considerations for future management

Abstract: Summary Increased regulation and extraction of water from rivers has contributed to the decline of fishes, and the use of environmental water allocations (EWAs) is now a key rehabilitation measure. Major reform of water policy in the Murray‐Darling Basin (MDB), Australia, has recently provided significant EWAs to improve ecological outcomes. Conflict over water buybacks, the value of the water and the need to maximise environmental benefits and minimise risks of unwanted outcomes has increased the expectation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 76 publications
(153 reference statements)
1
56
0
Order By: Relevance
“…Thus, our findings suggest that river reaches across the MDB that have more disturbed flow regimes are likely to support larger, more genetically diverse populations of Murray cod. Although this result seems counterintuitive because many native fish species are adversely affected by river regulation (Koehn et al, 2014), more consistent, perennial flows observed in regulated channels may reduce the frequency of population bottlenecks that can occur during the dry phases that typify the highly variable and unpredictable natural flow regime in the MDB . In the MDB the greatest disturbance to the natural flow regime typically occurs in lowland river reaches where river regulation and water extraction for irrigation support agricultural production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our findings suggest that river reaches across the MDB that have more disturbed flow regimes are likely to support larger, more genetically diverse populations of Murray cod. Although this result seems counterintuitive because many native fish species are adversely affected by river regulation (Koehn et al, 2014), more consistent, perennial flows observed in regulated channels may reduce the frequency of population bottlenecks that can occur during the dry phases that typify the highly variable and unpredictable natural flow regime in the MDB . In the MDB the greatest disturbance to the natural flow regime typically occurs in lowland river reaches where river regulation and water extraction for irrigation support agricultural production.…”
Section: Discussionmentioning
confidence: 99%
“…Flow-related variables are commonly identified as important predictors of species occurrence patterns in rivers, with flow considered a 'master variable' strongly associated with habitat complexity, geomorphology and many key physicochemical properties of rivers including temperature, pH and oxygen concentration (Poff et al, 1997). Disruption to a river's natural flow regime as a result of human activities (for example, flow regulation, construction of dams and weirs and water extraction) can have negative consequences for biodiversity, but may benefit some species Koehn et al, 2014). For example, in environments with highly variable and unpredictable natural flow regimes, flow-dependent species may benefit from artificially induced perennial flows .…”
Section: Introductionmentioning
confidence: 99%
“…Given that the long potential spawning season for carp can overlap with the environmental watering needs of many native fishes and other biota (vegetation, waterbirds; MDBA 2011) careful management of the associated risks relating to carp spawning and recruitment is needed. Managing environmental water is a relatively new science, particularly within an adaptive management framework; consequently, both scientists and managers need to continue to formally learn and garner knowledge from watering actions (Koehn et al 2014). The use of tools such as the population model demonstrated in this study, can assist this process by allowing scenario analysis and the exploration of the relative likely outcomes of alternative management actions so that can help tradeoffs can be evaluated.…”
Section: Use Of a Carp Population Model To Assist Adaptive Managementmentioning
confidence: 99%
“…High levels of water abstraction have placed significant pressure on aquatic ecosystems in the MDB, and many rivers are considered in poor health (Davies et al 2010). In response, environmental water allocations are now considered essential for the rehabilitation of its aquatic ecosystems (MDBA 2011;Koehn et al 2014) and initiatives such as the basin plan (MDBA 2011), are increasing the availability of environmental water (water delivered for environmental, not consumptive objectives; see Arthington 2012) in an attempt to rehabilitate riverine ecosystems, including native fishes (MDBA 2011;Koehn and Lintermans 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation